Pengaruh Kompetensi Akademik dan Motivasi Guru Terhadap Kinerja Guru - Arlita, Sulastri Eli; Ahyani, Nur; Missriani, Missriani (CV. Creative Tugu Pena, 2020)
This study determined whether there was an effect of academic competence on teacher’s performance, whether there was an effect of teacher’s motivation on teacher’s performance and whether there was an effect of academic competence and teacher’s motivation on the performance of junior high school teachers in Prabumulih Utara District. The sample of this research is civil servant teachers, consist of 59 teachers. The data were collected using questionnaire and documentation. The data analysis technique used the SPSS Version 21 software program application. The results of this study explain that there was an effect of academic competence on teacher’s performance, there is an effect of teacher’s motivation on teacher’s performance and there is an effect of academic competence and teacher’s motivation simultaneously on the performance of junior high school teachers in Prabumulih Utara District. Keywords: Teacher’s Motivation, Academic Competence, Teacher Performance